Development and Validation for Prednisolone in Tablet Dosage Form by Reverse Phase-HPLC - Ghosh, Somsubhra; Sathis Kumar, D.; Sahu, Anirban; Banji, David; Harani, A.; Krishna Chaitanya3, Ch.; Kalapana3, M. (Asian Journal of Chemistry, 2011)
A simple, economic, accurate reverse phase isocratic reverse phase-HPLC method was developed for the prednisolone (10 mg) in tablet dosage form. A hypersil ODS C18 (250 × 4.6 mm, packed with 5 micron) in an isocratic mode with mobile phase methanol:water (58:42) was used with flow rate (1.0 mL/min) and monitored at 254 nm. The retention times were 7.029 and 1.681 min for prednisolone and dexomethasone (internal standard), respectively. The linearity range was found to be 10-250 μg/mL. The proposed method was validated.